The specificity of rugby union training sessions in preparation for match demands - Campbell, P. G.; Peake, J. M.; Minett, G. M. (International Journal of Sports Physiology and Performance, 2018)
Purpose: Investigations into the specificity of rugby union training practices in preparation for competitive demands have predominantly focused on physical and physiological demands. The evaluation of the contextual variance in perceptual strain or skill requirements between training and matches in rugby union is unclear, yet holistic understanding may assist to optimize training design. This study evaluated the specificity of physical, physiological, perceptual, and skill demands of training sessions compared with competitive match play in preprofessional, elite club rugby union. Methods: Global positioning system devices, video capture, heart rate, and session ratings of perceived exertion were used to assess movement patterns, skill completions, physiologic, and perceptual responses, respectively. Data were collected across a season (training sessions n=29; matches n=14). Participants (n=32) were grouped in playing positions as: outside backs, centers, halves, loose forwards, lock forwards, and front row forwards. Results: Greater total distance, low-intensity activity, maximal speed, and meters per minute were apparent in matches compared with training in all positions (P<.02; d>0.90). Similarly, match heart rate and session ratings of perceived exertion responses were higher than those recorded in training (P<.05; d>0.8). Key skill completions for forwards (ie, scrums, rucks, and lineouts) and backs (ie, kicks) were greater under match conditions than in training (P<.001; d>1.50). Conclusion: Considerable disparities exist between the perceptual, physiological, and key skill demands of competitive matches versus training sessions in preprofessional rugby union players. Practitioners should consider the specificity of training tasks for preprofessional rugby players to ensure the best preparation for match demands.